Estuarine fishes associated with intertidal oyster reefs characterized using environmental DNA and baited remote underwater video. Issue 1 (27th February 2021) - Cole, Victoria J.; Harasti, David; Lines, Rose; Stat, Michael
Abstract: It has been widely shown that oyster reefs enhance local biodiversity and fisheries production. To determine the importance of intertidal remnant estuarine oyster reefs compared to unstructured sandy habitats over small spatial scales (<1 km) to fishes, assemblages were sampled with two nondestructive methods: baited underwater remote videos (BRUVs) and environmental DNA (eDNA) metabarcoding. Fish diversity from eDNA was characterized using three metabarcoding assays, and the assemblages differed with each, as well as to that detected by BRUVs. Overall, 112 fish genera were identified, with 78 more genera detected using eDNA metabarcoding than those observed with BRUVs. Both eDNA and BRUVs resolved a higher number of fish genera associated with oyster reefs than with sand sites, and a different fish composition between habitats was also resolved using each method. Furthermore, eDNA was shown to be useful toward characterizing the gamma diversity of the estuary, due to the intertidal nature and hydrodynamics of the system, as well as the alpha diversity associated with oyster reefs and sand sites. This study reinforces the importance of using multiple metabarcoding assays along‐side BRUVs for sampling assemblages of fishes and demonstrates the utility of using both methods in studies of biodiversity and future management of intertidal estuarine systems. Abstract : To determine the importance of intertidal remnant estuarine oyster reefs compared to unstructured sand habitats over small spatial scales (<1 km) to fishes, assemblages were sampled with two non‐destructive methods: baited underwater remote videos (BRUVs) and environmental DNA (eDNA) metabarcoding. Fish diversity from eDNA was characterised using three metabarcoding assays, and the assemblages differed with each, as well as to that detected by BRUVs. eDNA was shown to be useful towards characterising the gamma diversity of the estuary, due to the intertidal nature and hydrodynamics of the system, as well as the alpha diversity localised to the oyster reefs and sand sites.